A.S.P.E.N. Clinical Guidelines: Support of Pediatric Patients With Intestinal Failure at Risk of Parenteral Nutrition–Associated Liver Disease. (2nd April 2014) - Wales, Paul W.; Allen, Nancy; Worthington, Patricia; George, Donald; Compher, Charlene; ,; Teitelbaum, Daniel
Abstract : Background : Children with severe intestinal failure and prolonged dependence on parenteral nutrition are susceptible to the development of parenteral nutrition–associated liver disease (PNALD). The purpose of this clinical guideline is to develop recommendations for the care of children with PN‐dependent intestinal failure that have the potential to prevent PNALD or improve its treatment. Method : A systematic review of the best available evidence to answer a series of questions regarding clinical management of children with intestinal failure receiving parenteral or enteral nutrition was undertaken and evaluated using concepts adopted from the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) Working Group. A consensus process was used to develop the clinical guideline recommendations prior to external and internal review and approval by the American Society for Parenteral and Enteral Nutrition Board of Directors. Questions : (1) Is ethanol lock effective in preventing bloodstream infection and catheter removal in children at risk of PNALD? (2) What fat emulsion strategies can be used in pediatric patients with intestinal failure to reduce the risk of or treat PNALD? (3) Can enteral ursodeoxycholic acid improve the treatment of PNALD in pediatric patients with intestinal failure? (4) Are PNALD outcomes improved when patients are managed by a multidisciplinary intestinal rehabilitation team?